Genectic Variability In Some Maintainer Lines Of Hybrid Rice (Oryza sativa L) - Ansari, A; Rasul, MG; Biswas, PL; Paul, AK; Rahman, MH (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Twelve maintainer lines of rice were evaluated for 19 agronomic characters in a randomized complete block design to study the genetic divergence through multivariate analysis. Genotypes were grouped into three different clusters. Cluster I comprised maximum number of genotypes (ten) and II and III contain only single genotype each. PCA showed 70.29% variation against first three eigen values. The highest inter genotypic distance was observed between the genotype BRRI 1B and IR 73328B (2.278) followed by BRRI 3B and IR 68890B (2.229) and the lowest distance was observed (0.752) between genotypes BRRI 10B and IR 78355B followed by the distance (0.920) between genotypes BRRI 3B and IR 58025B. The inter cluster distance was larger than the intra cluster distances. The highest inter-cluster distance was observed between cluster II and III (7.113). The lowest inter-cluster distance was observed between cluster I and II (4.445) followed by cluster I and III (4.509). The inter cluster distances were higher than the intra cluster distances suggesting wider genetic diversity among the genotype of different groups. Among the characters anther length (0.00651), stigma length (0.00150), days to maturity (0.03018), number of tillers per hill (0.07890) and panicle weight (0.12713) were major characters that contribute to the genetic divergence. Key words: Rice; maintainer line; genotype; genetic divergence; D2 DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9323 Bangladesh J. Pl. Breed. Genet., 23(2): 35-40, 2010